2018
DOI: 10.15537/smj.2018.4.21749
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perception and attitudes towards oral care practices for mechanically ventilated patients

Abstract: Objectives:To explore the perception and attitudes of intensive care unit (ICU) nurses towards oral care practice for mechanically ventilated (MV) patients.Method:A descriptive cross-sectional design was used in this study. A convenience sample of 96 ICU nurses completed a questionnaire on their perception and attitudes towards oral care. The study setting was 3 representative Jordanian hospitals in Al-Karak and the capital, Amman, over a 6-month period between February and September 2016.Results:Ninety-six nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
26

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 34 publications
0
14
1
26
Order By: Relevance
“…17 Theory practice gap presents dearth in adherence to VCB as another study results showed poor nurses knowledge and sub-standard practices of VCB. 18 Similarly, another cross-sectional study was conducted in Iran and the results of the study revealed that the nurses' level of knowledge regarding VAP prevention guidelines was inadequate. 19 Conversely, a study conducted in Spain has revealed that nurses' knowledge about VAP preventive measures was good.…”
Section: Discussionmentioning
confidence: 99%
“…17 Theory practice gap presents dearth in adherence to VCB as another study results showed poor nurses knowledge and sub-standard practices of VCB. 18 Similarly, another cross-sectional study was conducted in Iran and the results of the study revealed that the nurses' level of knowledge regarding VAP prevention guidelines was inadequate. 19 Conversely, a study conducted in Spain has revealed that nurses' knowledge about VAP preventive measures was good.…”
Section: Discussionmentioning
confidence: 99%
“…Dua artikel menunjukkan bahwa perawat dan teknisi keperawatan gagal dalam merespon atau menerjemahkan pengetahuan dan praktek secara memadai (6,8) . Selain itu, terdapat 2 artikel yang mengatakan bahwa perawat perlu memperbaharui pengetahuan dan keterampilan perawatan mulut mereka dan setuju untuk mempelajari lebih lanjut tentang cara terbaik melakukan perawatan mulut (7,9) . Terdapat 1 artikel yang menunjukkan bahwa program kesehatan mulut dapat mengakibatkan peningkatan pengetahuan tentang kesehatan mulut yang signifikan (10) .…”
Section: Metodeunclassified
“…Satu artikel menyatakan sikap perawat positif terhadap perawatan mulut, namun mereka menganggapnya sebagai tugas yang tidak menyenangkan (9) . Satu artikel lainnya menunjukkan bahwa dari 11 pertanyaan mengenai sikap perawat, hanya 2 teknisi keperawatan yang mencapai 90% dari persyaratan (8) .…”
Section: Sikapunclassified
See 2 more Smart Citations